New Stability Indicating Ultrafast Liquid Chromatographic Method for the Determination of Sofosbuvir in Tablets (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: To develop a new sensitive, precise, simple, and economic stability indicating reverse phaseultrafastliquid chromatographic (RP-UFLC) method for the estimation of Sofosbuvir (SFB) in bulk andits tablet dosage forms. Materials and Methods: Chromatographic separation was achieved through C8Phenomenex column (250 mm × 4.6 mm i.d., 5 μm particle size) using acetonitrile: 0.1% Formic acid mixtureas the mobile phase. The Shimadzu model CBM-20A/20 Elite high-performance liquid chromatographysystem was monitored at detection wavelength 259 nm in isocratic mode with flow rate 0.8mL/min andthe total run time is 10 min. The method was validated, and forced degradation studies were conducted.Results and Discussion: SFB has obeyed Beer-Lambert’s law over a concentration range 1–200 μg/mL with correlation coefficient 0.9998. The limit of detection and limit of quantification are found to be0.2541 μg/ mL and 0.7642 μg/mL, respectively. The percentage relative standard deviation in precision andaccuracy studies was found to be